2021
DOI: 10.1002/hed.26922
|View full text |Cite
|
Sign up to set email alerts
|

Increased body mass index predicts prolonged survival in patients with head and neck squamous cell carcinoma

Abstract: Background: Higher body mass index (BMI) may have a protective effect on survival in patients with head and neck cancer. The aim of this study was to determine the effect of BMI on overall survival (OS) in veterans with head and neck squamous cell carcinoma (HNSCC).Methods: A cohort of 702 patients diagnosed with HNSCC between 1995 and 2019 were identified at the Washington DC Veterans Affairs Medical Center, and 342 patients were included for analysis. Records were queried for clinicaldemographic data, BMI, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…They also tend to have lower tolerance to the toxicities of cancer treatment [24,27]. As shown in this study, the adverse impact of a low BMI exerts an additive effect, with acute hemorrhage in patients with HNC, leading to a worse overall survival.…”
Section: Discussionmentioning
confidence: 69%
“…They also tend to have lower tolerance to the toxicities of cancer treatment [24,27]. As shown in this study, the adverse impact of a low BMI exerts an additive effect, with acute hemorrhage in patients with HNC, leading to a worse overall survival.…”
Section: Discussionmentioning
confidence: 69%
“…16,17 Veterans face unique challenges to care and have a disproportionate burden of comorbidities when compared to non-veteran populations. [18][19][20] Specifically, compared to the civilian population, veterans with HPVrelated HNSCC have higher rates of tobacco use and poor social support characteristics. 21,22 The high rate of comorbidities and variable support mechanisms among veterans place them at risk for poor outcomes when affected by a global pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, HNSCC may confer increased risks of both venous and arterial thromboembolism 16,17 . Veterans face unique challenges to care and have a disproportionate burden of comorbidities when compared to non‐veteran populations 18–20 . Specifically, compared to the civilian population, veterans with HPV‐related HNSCC have higher rates of tobacco use and poor social support characteristics 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been several studies evaluating the association between body mass index (BMI) and SCCHN risk, [8][9][10][11][12][13] few studies have evaluated the association between BMI and clinical outcomes in patients with SCCHN, [14][15][16][17][18][19][20] and the findings of these studies have been mixed. [14][15][16][17][18][19][20] Some studies found significant associations between low BMI and worse survival among patients with oral squamous cell carcinoma 14 and SCCHN, 18 and other studies found significant associations between higher BMI and better survival among patients with SCCHN, 16,18,19 patients with SCCHN treated with radiation, 20 and veterans with SCCHN. 15 In contrast, one study found that obesity was an adverse independent prognostic factor in early-stage squamous cell carcinoma of the oral tongue.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Some studies found significant associations between low BMI and worse survival among patients with oral squamous cell carcinoma 14 and SCCHN, 18 and other studies found significant associations between higher BMI and better survival among patients with SCCHN, 16,18,19 patients with SCCHN treated with radiation, 20 and veterans with SCCHN. 15 In contrast, one study found that obesity was an adverse independent prognostic factor in early-stage squamous cell carcinoma of the oral tongue. 17 Only a few studies have evaluated the association between BMI and clinical outcomes in patients with SCCHN stratified by tumor HPV status and subsite.…”
Section: Introductionmentioning
confidence: 99%